2015
DOI: 10.4236/as.2015.612147
|View full text |Cite
|
Sign up to set email alerts
|

Improving Grain Yield of Indigenous Rice in Tidal Floodplain of Southern Bangladesh: Effect of Seedling Age and Transplanting Method

Abstract: Rice production in the tidal floodplain of southern Bangladesh is constrained by uncontrolled water. In absence of high yielding varieties suitable for tidal floodplain, farmers grow low yielding indigenous cultivars of tall plant type. This paper reports the effect of agronomic management on the yield and yield components of an indigenous rice cultivar, Sadamota. The trial was conducted in 10 farmers' plots located widely apart in two upazila (sub-districts)-Jhalakati and Rajapur. 45 d and 60 d old seedlings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…However, the effectiveness of a rice transplanter is determined by the quality of the seedlings. Seedling density in the seedling tray influences seedling quality [20]. An optimal seeding density is essential to establish a sufficient plant population [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, the effectiveness of a rice transplanter is determined by the quality of the seedlings. Seedling density in the seedling tray influences seedling quality [20]. An optimal seeding density is essential to establish a sufficient plant population [21].…”
Section: Discussionmentioning
confidence: 99%
“…Baloch et al (2002) found an average number of plants per square meter of 114-169 plants. Hamid et al (2015) reported the number of plants per square meter as 149-156 plants, but beyond these results, our study indicated a minimum of 60.8-79.6 plants m -2 , and maximum of 132.3 plant m -2 required for economical grain yield to be attained according to the equation in Figure 1.…”
Section: Resultsmentioning
confidence: 44%
“…The development of a small number of standards, short duration, fertilizer responsive elite varieties of rice, because of the utilization of high yielding genotypes in a breeding program, has led to genetic erosion and, consequently, a remarkable loss of traditional heterogeneous cultivars (Hamid et al 2015;Jones et al 2008). For the development of a diverse population structure of rice, it is important to explore the genetic diversity within the population and among populations.…”
Section: Discussionmentioning
confidence: 99%